Evaluation of Dentin Tubule Occlusion Using Diode Laser and Shield Force Plus: A Comparative Study: Dentin tubule occlusion using diode laser and shield force plus - Salehpour, Samaneh; Rahmani, Marjan (Journal of Lasers in Medical Sciences, 2025)
Introduction: Dentin Hypersensivity is a dental short _lasting sharp pain originating from exposed dentin. This study investigated the level of dentinal tubule occlusion using a diode laser, the desensitizing agent Shield Force Plus, and the combined application of both treatments. Methods: Forty-five human premolar teeth, extracted due to orthodontic treatment plans or periodontal issues and confirmed to be free of caries, were collected for this study. The samples were sectioned to expose the outer third of the coronal dentin, and a rectangular area measuring 8 by 3 mm was delineated on each sample. The teeth were then allocated to five groups (n=9 per group): a negative control group (smear layer), a positive control group (smear layer removed), a group treated with the diode laser, a group treated with Shield Force Plus, and a group that received both the diode laser (wavelength 980 nm) and Shield Force Plus treatment. Imaging of the specimens was conducted using scanning electron microscopy at a 2000x magnification. Result: The group with the highest mean percentage of open dentinal tubules was the positive control group, which had an average of 10.52%. In contrast, the diode laser combined with the Shield Force Plus group exhibited the lowest average at 0.22%. The comparison revealed a significant difference between the laser group and the positive control group (P<0.001), as well as between the Shield Force Plus group and the positive control (P<0.001). No significant differences were found in dentinal tubule occlusion when comparing the effects of the diode laser, Shield Force Plus, and their combination (P>0.05). Conclusion: All three methods—diode laser application, Shield Force Plus, and their simultaneous use—effectively occluded dentinal tubules; however, none demonstrated superiority.